REFLEKSI AKTIVITAS MAHASISWA DALAM PERKULIAHAN DARING KIMIA DASAR MENGGUNAKAN ZOOM - Eliyarti Eliyarti; Chichi Rahayu (STKIP PGRI Situbondo, 2022)
One application that is widely used for online lectures is Zoom Meeting. This has an impact on changes in student activities during college. This type of research is quantitative descriptive, which aims to examine student activities during online learning of basic chemistry using Zoom. The sample of this study was the first-level students of the FT Ekasakti University in the Fundamental of Chemistry lectures in the odd semester 2020/2021. The data collection technique used is a non-test technique in the form of a questionnaire. Based on the results of data analysis, 75% of students stated that they had used the Zoom application before, student activities during online lectures included 68.75% recording important points of material presented by the lecturer, 43.75% asking questions and expressing opinions, 62.5% listening lecturer's explanation, 37.5% working on other course assignments, 87.5% turning off the camera so that the lecturer does not see the activity being done, 66.25% eating/drinking/snacking during online lectures, 47.5% daydreaming, 78.75% playing social media, and 72.5% more interested in paying attention to the screen display of friends compared to the display of the material explained by the lecturer. Inappropriate multitasking behavior can have a negative impact, causing students not to focus on online lectures. Students are expected to reduce activities that can interfere with their concentration during online lectures.